Reflections on editing a South African literary studies journal. Issue 4 (2nd October 2021) - Titlestad, Michael
Abstract: This article reflects on the history of English Studies in Africa, the journal published biannually since 1958 that is affiliated to the Department of English, University of the Witwatersrand, Johannesburg. My reflections, based on my 14-year editorship, are anecdotal. They are motivated by three considerations. First, journal editorship is a largely invisible practice in both institutions and across the literary studies academy, and it warrants comment because it is unduly influential. Second, anecdotes articulate situated experiences and practices. I am loath to make general inferences since each literary studies journal is embedded in its context and fashioned by distinct priorities, traditions, and routines. Nonetheless, this account will resonate in some respects with contributors and editors across the literary studies academy. Finally, changes at English Studies in Africa have refracted shifts in literary scholarship, which allows us to reflect, not just on the succession of critical paradigms, but on the effects of digitization, particularly the erosion of provincialism.